Investigation and Analysis of End-User Service Integrity in LTE/5G Fixed Wireless Access Networks in Macrocellular Environments - Muhammed, Aniru Abudu; Emagbetere, Joy Omoavowere (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2026)
Maintaining service integrity in fixed wireless access (FWA) networks requires reliable connectivity and thorough performance testing. This study compares LTE and 5G FWA in macrocellular environments by analyzing signal propagation, throughput, and latency. Field tests were conducted on post-production networks using 5G NR at 3.5 GHz and 2.5 GHz (43 dBm) and LTE at 3.5 GHz (31 dBm). The setup included customer premises equipment, measurement software, and a laptop, with all tests performed under Guaranteed Bit Rate conditions to ensure validity. Performance was evaluated using provisioned LTE and 5G SIMs with iPerf, QXDM, and Ping tools. Signal strength was measured against user terminal distance from the base station, while TCP traffic to an FTP server assessed uplink and downlink throughput under controlled conditions. The findings offer real-world insights to support improvements in FWA service quality and network reliability.